Transformational leadership and firm performance: a systematic literature review - Biniam Getnet Agazu; Chalchissa Amentie Kero; Kenenisa Lemi Debela (Journal of Innovation and Entrepreneurship)
Abstract This systematic literature review aims to investigate the influence of transformational leadership on firm performance and to establish a theoretical background for future avenues in literature. A total of 54 studies covering transformational leadership and firm performance from January 2016 to 2023 and analyzed via a Preferred Reporting Items for Systematic Reviews and Meta-Analysis protocol using the descriptive content analysis with relevant articles were documented following the inclusion and exclusion criteria. Studies were found in the Scopus, Web of Science, Taylor and Francis, and PubMed databases. The findings from this review show that a large majority of the reviewed studies conclude that transformational leadership has a positive relationship and influence on firm performance. This study will contribute to the literature on leadership effectiveness and inform organizational practices aimed at enhancing firm performance through transformational leadership through mediating variable of dynamic capability and organizational innovation. Despite a rapid recent increase in publications and special issue calls, many opportune research avenues within the transformational leadership and firm performance on different research methods need further investigation.